Approaching the peasant world - Briggs, Miguel (1984)
The preferential option for the poor is an evangelical challenge for all the disciples of Jesus. It implies a process of assuming the cause of the poor, of solidarity in their struggle and of approaching their world. In many sectors of the continent there is a great effort by pastoral agents to pitch their tent in the midst of the poor, to live discipleship from a life side by side with the poor. In this article I would like to describe some key points of the experience in the peasant community and its implications in the construction of the Church.